2009
DOI: 10.1242/dev.038422
|View full text |Cite
|
Sign up to set email alerts
|

The cell adhesion molecules Echinoid and Friend of Echinoid coordinate cell adhesion and cell signaling to regulate the fidelity of ommatidial rotation in theDrosophilaeye

Abstract: Directed cellular movements are a universal feature of morphogenesis in multicellular organisms. Differential adhesion between the stationary and motile cells promotes these cellular movements to effect spatial patterning of cells. A prominent feature of Drosophila eye development is the 90°rotational movement of the multicellular ommatidial precursors within a matrix of stationary cells. We demonstrate that the cell adhesion molecules Echinoid (Ed) and Friend of Echinoid (Fred) act throughout ommatidial rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…6C). The dynamic and differential expression of Ed (and of its paralog Friend of Echinoid) in the rotating clusters and non-rotating ICs has also been proposed to modulate ommatidial rotation (Fetting et al, 2009). Thus, differential expression of Ed, Fmi, DE-cad and Friend of Echinoid in the rotating clusters and non-rotating ICs prevents the homotypic interaction of these four CAMs to allow free rotation of photoreceptor clusters.…”
Section: Ed and Pcpmentioning
confidence: 99%
See 2 more Smart Citations
“…6C). The dynamic and differential expression of Ed (and of its paralog Friend of Echinoid) in the rotating clusters and non-rotating ICs has also been proposed to modulate ommatidial rotation (Fetting et al, 2009). Thus, differential expression of Ed, Fmi, DE-cad and Friend of Echinoid in the rotating clusters and non-rotating ICs prevents the homotypic interaction of these four CAMs to allow free rotation of photoreceptor clusters.…”
Section: Ed and Pcpmentioning
confidence: 99%
“…Fetting et al recently showed that ed genetically interacts with Egfr pathway members, and proposed that ed, via inhibiting Egfr signaling in the photoreceptors, regulates ommatidial rotation (Fetting et al, 2009). However, we demonstrated that, after row 2, Ed facilitates the endocytosis of Egfr only in the non-rotating ICs, but not in the photoreceptor clusters (Fig.…”
Section: Ed and Pcpmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, two additional cell adhesion molecules, the IgCAM Echinoid (Ed), capable of homophilic and heterophilic interactions (Islam et al ., 2003), as well as its paralog Fred (Friend of Echinoid), have recently been described to be required for proper rotation (Fetting et al ., 2009; Ho et al ., 2010). While loss of their function causes a wide variation in the rotation angle of individual ommatidia, genetic interactions showed that ed and fred antagonistically interact with the EGFR signaling components pointed and canoe (Fetting et al ., 2009).…”
Section: The Core Pcp Pathway and Its Effectorsmentioning
confidence: 99%
“…While loss of their function causes a wide variation in the rotation angle of individual ommatidia, genetic interactions showed that ed and fred antagonistically interact with the EGFR signaling components pointed and canoe (Fetting et al ., 2009). Ed is a known inhibitor of EGFR signaling in other contexts (Bai et al ., 2001), but enhances rotation defects of pnt and cno (Fetting et al ., 2009). In contrast, fred mutations suppress loss of cno or pnt , again pointing toward a tight interplay between EGFR signaling, cell adhesion, and rotation.…”
Section: The Core Pcp Pathway and Its Effectorsmentioning
confidence: 99%